2013
DOI: 10.1007/s12262-013-0875-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of Amnion Transfer in Resistant Nonhealing Venous Leg Ulcers

Abstract: In the treatment of venous leg ulcers, after adopting many treatment modalities, at times we are still left with a local indolent problem, "the resistant nonhealing venous ulcer." With repeated surgical procedures failing to obtain a healed ulcer, constant pain, persistent discharging wound, infections, etc., many a patient turn hostile. Also, there comes a dimension of despair in the health feeling of the patient. This prospective study was conducted in 40 patients, who were within the inclusion criteria (Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In one RCT [17] a notable reduction in the baseline surface area of the ulcers in patients treated with HAM was observed. A prospective study conducted by Francis et al [19] demonstrated less than a 30% of recurrence rate of venous leg ulcers during a 3-year followup period. Furthermore, Hanumanthappa et al [20] in their prospective comparative study have shown that 80% of ulcers achieved epithelialization at 3 weeks with HAM dressing and it was statistically significant.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In one RCT [17] a notable reduction in the baseline surface area of the ulcers in patients treated with HAM was observed. A prospective study conducted by Francis et al [19] demonstrated less than a 30% of recurrence rate of venous leg ulcers during a 3-year followup period. Furthermore, Hanumanthappa et al [20] in their prospective comparative study have shown that 80% of ulcers achieved epithelialization at 3 weeks with HAM dressing and it was statistically significant.…”
Section: Resultsmentioning
confidence: 97%
“…We found 3 randomized control trials [16,17,18] and all were multicenter trials conducted in the United States. Out of 4 prospective studies, 2 were done in India [19,20] and one each in France [21] and Spain [22].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At week 16, the mean VLU area was reduced by 72% for allograft-treated wounds compared to 39% with standard of care. In a 2013 prospective study, 40 patients with non healing venous ulcers were observed for one to three years following an amniotic membrane (AM) transfer 19 . The inclusion criteria for this study included; patients between 40-50 years of age, non healing venous leg ulcers 3cm in size or greater, ulcer duration greater than 3-months despite surgery or split skin graft.…”
Section: Discussionmentioning
confidence: 99%